1999
DOI: 10.1046/j.1471-4159.1999.720868.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Distribution of Ferritin Binding Sites in the Adult Mouse Brain

Abstract: Studies on iron uptake into the brain have traditionally focused on transport by transferrin. However, transferrin receptors are not found in all brain regions and are especially low in white matter tracts where high iron concentrations have been reported. Several lines of research suggest that a receptor for ferritin, the intracellular storage protein for iron, may exist. We present, herein, evidence for ferritin binding sites in the brains of adult mice. Autoradiographic studies using 125 Irecombinant human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 47 publications
5
59
0
2
Order By: Relevance
“…These ®ndings imply that there might be some other mechanisms involved in the regulation of maternal-fetal iron transport. Previous studies have demonstrated that FnR, in addition to TfR, is present on the membranes of many normal cells (Moss et al, 1992), including reticulocytes (Blight and Morgan, 1987a), lymphoblasts (Adams et al, 1992), liver (Moss et al, 1988) and brain cells (Adams et al, 1992;Ramm et al, 1994;Hulet et al 1999). This protein is also found to play a role in iron transport across the membrane of these cells (Blight and Morgan, 1987b;Moss et al, 1988;Osterloh & Aisen, 1989;Gelvan et al, 1996) and ferritin uptake by human erythroid precursors is a regulated iron The results are meansAE s.d.…”
Section: Discussionmentioning
confidence: 99%
“…These ®ndings imply that there might be some other mechanisms involved in the regulation of maternal-fetal iron transport. Previous studies have demonstrated that FnR, in addition to TfR, is present on the membranes of many normal cells (Moss et al, 1992), including reticulocytes (Blight and Morgan, 1987a), lymphoblasts (Adams et al, 1992), liver (Moss et al, 1988) and brain cells (Adams et al, 1992;Ramm et al, 1994;Hulet et al 1999). This protein is also found to play a role in iron transport across the membrane of these cells (Blight and Morgan, 1987b;Moss et al, 1988;Osterloh & Aisen, 1989;Gelvan et al, 1996) and ferritin uptake by human erythroid precursors is a regulated iron The results are meansAE s.d.…”
Section: Discussionmentioning
confidence: 99%
“…The homogenate was centrifuged at 29,000 g for 10 min at 4°C. The resulting supernatant was aspirated and the pellet (representing the membranes) was resuspended with the original volume of buffer and then placed in a 37°C incubator for 30 min to promote the release of endogenous ferritin from the tissue prepara- Hulet et al [1999a]. Each value was obtained from binding experiments on at least 3 brains (each in duplicate) and is expressed as the mean B standard error.…”
Section: Membrane Preparationmentioning
confidence: 99%
“…[18][19][20][21][22] Evidence for the presence of a ferritin-receptor has been derived initially from cellular ferritin-binding and -uptake assays and binding of ferritin in tissue sections where binding was specific mostly for H-subunit rich ferritin. 19,[23][24][25] 21,26 and was identified in embryonic kidney and adult testis epithelial cells. 28 Early characterizations of serum ferritin were performed mainly on human serum ferritin from iron-overloaded patients.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22] Evidence for the presence of a ferritin-receptor has been derived initially from cellular ferritin-binding and -uptake assays and binding of ferritin in tissue sections where binding was specific mostly for H-subunit rich ferritin. 19,[23][24][25] Three distinct candidates for ferritin-receptors have been characterized and cloned recently. TIM-2 26 is a murine ferritin-receptor that specifically binds H-subunit and is primarily expressed on splenic B cells, epithelial cells of the bile duct, and kidney distal tubular cells.…”
Section: Introductionmentioning
confidence: 99%